PENERAPAN ANALISIS VARIANS (ANOVA) SEBAGAI STRATEGI OPTIMAL-ISASI EVALUASI KOMPARATIF DALAM PENELITIAN PENDIDIKAN: SEBUAH REVIEW KRITIS TERHADAP PRAKTIK, PROBLEM, DAN PROSPEK - Rini Kurniatun Sari; Vivi Ida Septina; Zulkarnain; Edy Waluyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The accuracy of data analysis in quantitative educational research is a determinant of the validity of scientific decisions. This study aims to analyze the implementation, procedures, urgency, and limitations of using Analysis of Variance (ANOVA) as a method for comparative evaluation of more than two groups in the educational context. This study used a comprehensive literature review method by analyzing articles and reference books relevant to statistical applications in education published up to 2026. The results showed that ANOVA provides a significant advantage in reducing Type I errors compared to repeated t-tests. One-Way ANOVA and Two-Way ANOVA are the most relevant types used to evaluate the effectiveness of learning models and media simultaneously. However, its implementation is highly dependent on strict parametric assumptions, namely normality, homogeneity, and data independence. This study implies that a comprehensive understanding of ANOVA procedures, explicit mathematical formulation, post-hoc tests, and mitigation strategies for violated assumptions is essential for educational researchers to produce objective and accountable conclusions